2011
DOI: 10.1136/bcr.05.2011.4181
|View full text |Cite
|
Sign up to set email alerts
|

Posterior reversible encephalopathy manifested by refractory status epilepticus in two patients under chemotherapy

Abstract: DESCRIPTIONPosterior reversible encephalopathy (PRES) is a clinicalradiological syndrome characterised by brain symmetric lesions of vasogenic oedema, in white matter, basal ganglia or cerebral cortex, preferentially in posterior topography. 1 Typical manifestations are headache and altered mental status. Epileptic seizures are also frequent, although status epilepticus (SE) is a rare occurrence. 2 Chemotherapy may trigger PRES. Nevertheless, no single chemotherapy agent was consistently implicated. 2 Two case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…PRES has previously been reported in patients with HL; however, no single chemotherapeutic agent has consistently been implicated. 5,12 In our patient, the decision was to eliminate a single agent in order to assess resultant changes in neurological symptoms and MRI findings. Vinblastine was the first chemotherapeutic agent to be eliminated due to its association with peripheral neuropathy and the fact that vinca alkaloids are reported to be associated with PRES within the month preceding PRES.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PRES has previously been reported in patients with HL; however, no single chemotherapeutic agent has consistently been implicated. 5,12 In our patient, the decision was to eliminate a single agent in order to assess resultant changes in neurological symptoms and MRI findings. Vinblastine was the first chemotherapeutic agent to be eliminated due to its association with peripheral neuropathy and the fact that vinca alkaloids are reported to be associated with PRES within the month preceding PRES.…”
Section: Discussionmentioning
confidence: 99%
“…As vinblastine has been associated with peripheral neuropathy, PRES has been reported in patients with HL undergoing ABVD treatment. 5 Here, we present a case of vinblastine-associated PRES in a patient with HL.…”
Section: Introductionmentioning
confidence: 95%
“…Seizures are usually generalized and they occur in the acute stage of the disease, that commonly resolve within days. Refractory status epilepticus is a rare occurrence in PRES [ 4 , 5 ]. The treatment of PRES is aimed to identify underlying causes of the syndrome, and to control hypertension and seizures.…”
Section: Discussionmentioning
confidence: 99%
“…Raj et al ., in a study of 8 pediatric patients with PRES of diverse causes, found predominant generalized tonic and/or clonic seizures with no neurological sequel after 1 year follow up. 6 PRES presenting as status epilepticus has been documented in a previously healthy child, 7 two patients on chemotherapy, 8 after pediatric hematopoietic stem cell transplantation in 10 patients and in a further 10 cases where focal-onset complex partial seizure was present in the majority of cases. 9 PRES, in addition, can cause both convulsive and non-convulsive status epilepticus.…”
Section: Discussionmentioning
confidence: 99%